The Learning Outcomes Of Students That Experience The Cooperative Learning Model Make A Match Offline And Online - James U.L. Mangobi; Vivian E. Regar; Yunike Manopo (Departement of Mathematics Education, 2023)
This research aims to determine the differences in the learning outcomes of students who experience the Make a Match (MAM) type of cooperative learning model offline and students who experience the online MAM type cooperative learning model in terms of their academic abilities. This research was conducted at the Tombatu Christian Vocational School in the even semester of the 2020/2021 academic year. The research method used is quasi-experimental, and the research design used is a two-factor analysis of variance. The research object was 18 students in class X of the Nursing Department using the MAM-type cooperative learning model offline and 20 students in class X of the Computer and Network Engineering Department (TKJ) using the MAM-type cooperative learning model online. The research instrument used was a test of learning outcomes through an essay. The study results show that: (1) There are significant differences in the learning outcomes of students with high academic ability in classes that experience the offline MAM-type cooperative learning model and online MAM. The learning outcomes of students with high academic abilities who study offline are better than those who study online. (2) There is a significant difference in the learning outcomes of students with low academic ability in classes that experience the MAM-type cooperative learning model offline and online. The learning outcomes of students with low academic ability who study offline are better than those who study online. (3) Significant differences exist in student learning outcomes in classes that experience the offline and online MAM-type cooperative learning model. The learning outcomes of students who study offline are better than those of online students.